The Long-Time Behavior of the Ricci Tensor under the Ricci Flow. (19th September 2013) - Hilaire, Christian
Abstract : We show that, given an immortal solution to the Ricci flow on a closed manifold with uniformly bounded curvature and diameter, the Ricci tensor goes to zero as t → ∞ . We also show that if there exists an immortal solution on a closed 3-dimensional manifold such that the product of the curvature and the square of the diameter is uniformly bounded, then this solution must be of type III.